2013
DOI: 10.1073/pnas.1217020110
|View full text |Cite
|
Sign up to set email alerts
|

Control of transposon activity by a histone H3K4 demethylase in rice

Abstract: Transposable elements (TEs) are ubiquitously present in plant genomes and often account for significant fractions of the nuclear DNA. For example, roughly 40% of the rice genome consists of TEs, many of which are retrotransposons, including 14% LTR-and ∼1% non-LTR retrotransposons. Despite their wide distribution and abundance, very few TEs have been found to be transpositional, indicating that TE activities may be tightly controlled by the host genome to minimize the potentially mutagenic effects associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(65 citation statements)
references
References 55 publications
2
57
0
Order By: Relevance
“…The jmj703 mutation resulted in a change of a relatively small portion of genome-wide H3K4me3 (Figure 5F), which confirmed previously published data (Cui et al, 2013), but led to a loss of 2957 and a gain of 2447 H3K27me3-marked genes in IM ( Figure 5E). Comparison of differentially marked genes in jmj703 and SDG711 RNAi plants revealed that 2307 out of 2952 (i.e., 2307 + 645) (78%) genes that lost H3K27me3 in jmj703 overlapped with those that lost the mark in SDG711 RNAi plants, 50% of which (1172/2307) corresponded to the genes that gained the mark in wild-type IM ( Figures 5A and 5E).…”
Section: Functional Relationship Between Sdg711 and Jmj703 In H3k27mesupporting
confidence: 89%
“…The jmj703 mutation resulted in a change of a relatively small portion of genome-wide H3K4me3 (Figure 5F), which confirmed previously published data (Cui et al, 2013), but led to a loss of 2957 and a gain of 2447 H3K27me3-marked genes in IM ( Figure 5E). Comparison of differentially marked genes in jmj703 and SDG711 RNAi plants revealed that 2307 out of 2952 (i.e., 2307 + 645) (78%) genes that lost H3K27me3 in jmj703 overlapped with those that lost the mark in SDG711 RNAi plants, 50% of which (1172/2307) corresponded to the genes that gained the mark in wild-type IM ( Figures 5A and 5E).…”
Section: Functional Relationship Between Sdg711 and Jmj703 In H3k27mesupporting
confidence: 89%
“…Moreover, JmjCmediated histone demethylation at the FLC locus at elevated temperature is known to prevent premature early flowering (Gan et al, 2014). In rice, the JMJ703, a histone H3 Lys 4 (H3K4) demethylase, is required for stem elongation and transposon silencing (Chen et al, 2013;Cui et al, 2013). The barley VRS3 is similar to the JMJD2 group II of Lys demethylases and exhibits a high similarity to the rice JMJ706, which encodes for a histone H3 Lys 9 di-and tri-(H3K9me2 and H3K9me3) demethylase (Sun and Zhou, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Plant jmjC proteins are generally conserved with yeast and animal homologs, while there exist a subgroup of more divergent jmjC proteins (Sun and Zhou, 2008). Members of this subgroup (i.e., Arabidopsis JMJ14, JMJ15, and JMJ18 and rice JMJ703) have been reported to be H3K4 demethylases and to regulate diverse aspects of chromatin function and plant development (Deleris et al, 2010;Lu et al, 2010;Searle et al, 2010;Yang et al, 2012aYang et al, , 2012bChen et al, 2013;Cui et al, 2013). Conversely, the JMJD3/UTX (ubiquitously transcribed tetratricopeptide repeat, X chromosome) subgroup proteins, which exhibit H3K27 demethylase activities in mammalian cells, are not found in plants.…”
Section: Introductionmentioning
confidence: 99%